Evaluating the Knowledge of Computed Tomography Parameters between Radiographers and Undergraduate Students in Medina, Saudi Arabia - Qurashi, Abdulaziz; Alsharif, Walaa; Alshoabi, Sultan; Almohsen, Nasser; Aljohani, Saeed; Banoqitah, Essam; Subahi, Ahmad; Aldahery, Shrooq; Alshamrani, Khalid (Journal of King Abdulaziz University: Engineering Sciences, 2022)
This study aims to evaluate employees (i.e., radiographers) and undergraduate students’ knowledge of Computed Tomography (CT) parameters and their impact on image quality and radiation dose. A cross-sectional questionnaire study was conducted at four hospitals in Medina, KSA. The survey consisted of 12 close-ended multiple-choice questions related to computed tomography technical parameters. The survey was distributed with a comprehensive explanation to the respondents, and all of the responses remained anonymous with no questions related to identity were asked. Forty respondents were included in this study. Of those, 14 students were from level eight, 11 students were from level six, nine were interns and six were employees. There was a twofold difference in the answers between undergraduate students and radiographers despite the experience gap between both groups. Students were able to answer most of the questions correctly. Only few questions sparked controversy due to the major difference of answers when both groups were compared. The understanding level of the respondents varies among students and employees, where most of the correct answers were given by the former. The main reason for this could be due to the variation in the respondents’ qualification. The employees in this study were only technicians with diploma degree.